MOTIF ANGGOTA MENGIKUTI KOMUNITAS MOTOR VIXION YVCI DI KOTA PADANG (Studi kasus : Komunitas di Jalan Samudera Kelurahan Belakang Tangsi Kecamatan Padang Barat) - Rukmini, Rina - (Pendidikan Sosiologi, 2014)
Motorcycle has become a necessity for the community, along with thetimes this brings about changes to the mindset and attitude of the people indeveloping life. In the motorcycle community in general is used to simplify andspeed up the person in traveling, now this bike is not only regarded as a meremeans of transportation, but at the present time the motorcycle was alsoinstrumental in the development of modern society, which in turn can form asocial life variegated. Even when this is not uncommon for people to usemotorcycles to an assembly that the motorcycle community for the sake of goodrelations among motorcyclists. This study aimed to describe patterns of motorVixion community members follow YVCI in padang cityThe theory used in this study is a phenomenological theory developed byAlferd Schutz. According to Schutz Alferd human action is determined by themeaning that is understood about something called the motif, which Schutz splitinto two parts, namely motif Because motive motive and in order. Informants inthis study are members of the community who follow the motorcycle VixionYVCI in Padang. The informants in this study were 13 members of themotorcycle community Vixion YVCI. Selection of informants through purposivesampling, that the withdrawal of the informants were purposively selected by theresearcher. The research method is observation, interview and documentation.Translating is tested using triangulation of data, the data were analyzed with aninteractive model that consists of data reduction, data presentation and conclusion.The findings in the field that follows the members of the motorcyclecommunity motives Vixion YVCI are (1) In order motive (a) Adding a lot offriends, (b) Pioneer of traffic safety, (c) Hobby (touring) (2) Because of motive (a)More know about motorcycles, (b) Relieve stress.